El avance tecnológico y el incremento del bullying en los adolescentes de las instituciones educativas públicas en la ciudad de Huánuco. Periodo – 2013 - Dionisio Vara, Adler (2017)
Present work shows the phenomenon of the bullying or harassment student for which many students cross. The bullying is a self-assertion, a behavior that it is reiterated toward deliberate, - intentional- manner someone else; He is a harassment, a persistent intimidation toward another companion. That is, negative derivations in the personality’s development and the socialization, that they can affect ordinary development of life quotidian and the school. Cases, suicide enclosure of boys (to) for the suffering through situations caused of bullying Exist. To the respondiendo himself them pregunt: ¿have you gotten bullying some companion, occasionally utilizing the Internet? Her students IE Hermilio Valdizan respond than SI in one 25. Them IE Leoncio Prado affirm than SI of her, (53) her students the Mercies’s IE Our Lady they say to than Si (33 %) and her students IE Illatupa confirm than SI with one 20. In the bullying, there is one hurter or varied, and one once was hurt, he is who white of the harassment or aggression, verbal or physical. The aftereffects of the bullying in the battered or victims are painful, they can vary from the self-esteem’s deterioration, anxiety, phobia riots student and enclosure depression. Present work intends to make known this information with the enthusiasm of creating conscience among our society and with it to look for a decrease or prevention of the harassment among equals in our country’s educational institutions. I ask around to them to him to the students of the educational institutions polled¿How does the bullying in the high school or your living-room of classrooms become manifest? Her students IE Hermilio Valdizan responded: They exclude him to be ugly 14. Her students IE Leoncio Prado, they exclude him to be ugly 40. Her students the Mercies’s IE Our Lady, they exclude him to be ugly 7. They exclude him because he is poor 29. Her students IE Leoncio Prado, they exclude him to be ugly 40. Her students the Mercies’s IE Our Lady, they exclude him to be ugly 7 they exclude him to be of the saw 79. They exclude him because 14 is poor, And her students IE Illatupa, they exclude him to be ugly 10. Besides were asked ¿He has increased to me in your high school the 90 They exclude him because he is poor 0. Besides were asked ¿He has increased to me In your high school the Bullying for Internet? They answer in shape mayoritaria. her students IE Hermilio Valdizan respond than SI in one 64. Them IE Leoncio Prado affirm than SI of her, 64 her students the Mercies’s IE Our Lady they say to than Si 40, And her students IE Illatupa confirm than SI with one 73.